The lord of the rings – the fellowship of the ring: a comparative analysis of the book and the screenplay - Araujo, Raquel Casco (Universidade do Vale do Rio dos Sinos, 2021)
This final thesis seeks to undertake a literary comparative analysis of the book The Lord of the Rings – The Fellowship of the Ring (2004) by J. R. R. Tolkien and the screenplay of the movie The Lord of the Rings – The Fellowship of the Ring (c2001) whose screenwriters are Fran Walsh, Philippa Boyens, and Peter Jackson. Most studies on adaptation and literature are about the book and the movie; however, it is important to highlight that the script is the one being analyzed and compared in this thesis, even though the movie is mentioned and used to complement the analysis and the final remarks. This work is organized in four chapters. The first chapter is the introduction, which states the objectives of this project and its importance. The second chapter – the theoretical background – is divided into two subchapters. The first subchapter focusses on the theories of adaptation and presents several lenses of adaptation which include Hutcheon (2006), Stam (2000a), Balázs (1953), Bazin (1967), Andrew (1984), Bluestone (1961), Kraucauer (1960), Mitry (1971), and Leitch (2007). The second one gives an overview of the script and explains how it was turned into a screenplay. The third chapter is dedicated to the comparative analysis of the book and the screenplay through its similarities and differences – more specifically, the similarities and the differences regarding narrator, language, characters and characterization, plot, and poetic insertions. The fourth chapter presents the final remarks arising from thesis which aligns with the theories of Hutcheon (2006), Stam (2000a), Balázs (1953), Bluestone (1961) and Mitry (1971) which portrays an adaptation as a new entity containing a kernel of truth (concerning the main source). Furthermore, I encourage new studies in the literary and cinematic areas.
Keywords: The lord of the rings; Literature; Adaptation; Screenplay; Comparison; O Senhor dos anéis; Literatura; Adaptação; Roteiro; Comparação